2013
DOI: 10.1002/icd.1788
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Commentaries

Abstract: In our response, we address four themes arising from the commentaries. First, we discuss the distinction between cognition and metacognition and show how to draw it within our framework. Next, we explain how metacognition differs from social cognition. The underlying mechanisms of metacognitive development are then elucidated in terms of interaction patterns. Finally, we consider measures of metacognition and suitable methods for investigating it. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example, Proust (2007) developed a model of implicit metacognition considered as an adaptive control system consisting of regulated and regulating subsystems, which does not require the involvement of metarepresentation. Elaborating further along partly similar lines, Brinck and Liljenfors (2013a, b) differentiated between implicit metacognition, perceptual metacognition, and metarepresentational metacognition. Implicit and perceptual metacognition are assumed to rely on heuristics and environmental affordances, without any use for algorithms and metarepresentations.…”
Section: The Development Of Mentalization and Its Dimensionsmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, Proust (2007) developed a model of implicit metacognition considered as an adaptive control system consisting of regulated and regulating subsystems, which does not require the involvement of metarepresentation. Elaborating further along partly similar lines, Brinck and Liljenfors (2013a, b) differentiated between implicit metacognition, perceptual metacognition, and metarepresentational metacognition. Implicit and perceptual metacognition are assumed to rely on heuristics and environmental affordances, without any use for algorithms and metarepresentations.…”
Section: The Development Of Mentalization and Its Dimensionsmentioning
confidence: 76%
“…The mentalization literature contains no application of the implicit/explicit distinction to metacognition. Models of implicit metacognition have, however, been outlined by Proust (2007) and Brinck and Liljenfors (2013a, b). Further, the latter writers have suggested that primary intersubjectivity plays a role in the development of metacognition.…”
Section: Intersubjectivity and Mentalizationmentioning
confidence: 99%